2020
DOI: 10.1039/d0cp03282d
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of supramolecular hollow nanotubes with atomistic simulations and SAXS

Abstract: Self-assembled nanostructures arise when building blocks spontaneously organize into ordered aggregates that exhibit different properties compared to the disorganized monomers. Here, we study an amphiphilic cyanine dye (C8S3) that is...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…The boundary distance of the DWNTs of 13.6 ± 0.4 nm agrees with the values published in the literature 6 , 13 , 21 , 22 . The wall thickness, evaluated from the difference between the boundary distances of DWNTs and flash-diluted NTs, is (13.6–10.2)/2 = 1.7 nm, which agrees well with the size of C8S3 molecule (∼2 nm) 23 considering the interdigitating aliphatic tails 21 .…”
Section: Resultssupporting
confidence: 90%
“…The boundary distance of the DWNTs of 13.6 ± 0.4 nm agrees with the values published in the literature 6 , 13 , 21 , 22 . The wall thickness, evaluated from the difference between the boundary distances of DWNTs and flash-diluted NTs, is (13.6–10.2)/2 = 1.7 nm, which agrees well with the size of C8S3 molecule (∼2 nm) 23 considering the interdigitating aliphatic tails 21 .…”
Section: Resultssupporting
confidence: 90%
“…A large number of biological phenomena are now accessible for computational analysis, ranging from biomolecular dynamics, enzymatic processes, and virus assembly to the structure of small organelles [ 12 , 13 , 14 ], making computer simulation techniques an indispensable tool. Additionally, they are used for biomolecular engineering and drug design [ 15 , 16 , 17 , 18 ], Nevertheless, all computational methods have their strength in specific ranges of time and length scales, while they are inapplicable outside these ranges. Therefore, for many biological processes, several of these methods must be put into play.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, nanotubes and a nanotube bundle with length ∼50 nm (∼3650-6000 and ∼16000 molecules, respectively) were constructed and solvated in rectangular boxes. The C8S3 nanotubes were constructed by creating 2D-lattices from an initial unit cell and, then, rolling the lattices into cylindrical shapes 20,21 . The initial unit cell was obtained from the crystal structure of a cyanine dye with the same aromatic core as the C8S3 molecule 32 , and the original molecules were replaced with C8S3 molecules at CG level.…”
Section: Simulations -Cgmentioning
confidence: 99%
“…The diameters of the designed systems ranged from 12 to 17 nm, close to the reported experimental values in the literature for the nanotube diameter vary from 13 to 17 nm 10,46 . Previous atomistic MD studies showed that preformed nanotubes with different diameter can be stable, as long as the nanotube thickness and the initial monomer arrangement is reasonable 20,21 . All systems were constructed with an initial double-wall thickness of ∼2.5 nm, which remained roughly the same in all simulations.…”
Section: Preformed Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation